2018
DOI: 10.1097/jom.0000000000001186
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Induced Hearing Loss in Shipyard Workers

Abstract: Simultaneous exposures classified as high for metals/solvents/noise appear to damage hearing more than exposure to noise alone. Hearing conservation programs should take into consideration combined exposures to metals, solvents, and noise, not simply exposure to noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Researchers’ postulated NIOSH STS evaluation (method 3) is potentially more sensitive in the evaluation of ototoxic effects because of the inclusion of the 500, 1000, and 6000 Hz frequencies (compared to other PTA evaluation methods that omit these frequencies) and the usage of absolute shifts by independent frequency instead of averaging values. These results are consistent with Schaal et al (2018) who found significantly higher levels of hearing loss when considering dB HL at 500 to 6000 Hz in an industrial workforce due to exposure to ototoxicants such as lead, cadmium, and arsenic at OSHA Action Levels and ototoxicants such as toluene and xylene at sub-OEL concentrations. Chang et al (2006) found similar results due to combined toluene and noise exposure that increased hearing thresholds at 1000 and 2000 Hz.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Researchers’ postulated NIOSH STS evaluation (method 3) is potentially more sensitive in the evaluation of ototoxic effects because of the inclusion of the 500, 1000, and 6000 Hz frequencies (compared to other PTA evaluation methods that omit these frequencies) and the usage of absolute shifts by independent frequency instead of averaging values. These results are consistent with Schaal et al (2018) who found significantly higher levels of hearing loss when considering dB HL at 500 to 6000 Hz in an industrial workforce due to exposure to ototoxicants such as lead, cadmium, and arsenic at OSHA Action Levels and ototoxicants such as toluene and xylene at sub-OEL concentrations. Chang et al (2006) found similar results due to combined toluene and noise exposure that increased hearing thresholds at 1000 and 2000 Hz.…”
Section: Discussionsupporting
confidence: 91%
“…This study reported a 70% increased OR despite organic solvent mixture exposures being estimated below OELs (Kaufman et al 2005). Evaluating exposures for civilians conducting shipyard work, Schaal et al (2018) assessed 1266 personnel exposed to high/low concentration combinations of noise, ototoxic solvents, and ototoxic metals. Results identified significantly greater hearing level shifts at 2000 Hz, shifts averaged across 2000 to 4000 Hz, and shifts averaged across 500 to 6000 Hz for high metal/solvent compared to low metal/solvent groups with similar noise exposures (Schaal et al 2018).…”
Section: Ototoxicantsmentioning
confidence: 99%
“…Estudo recente identificou relação estatisticamente significativa entre os níveis de tolueno e maior possibilidade de acometimento de perda auditiva nas altas frequências (Staudt et al, 2019). Além disso, sabese que a exposição a fatores combinados (ruído e produtos químicos) costuma ser mais danosa do que a exposição exclusiva ao ruído (Schaal et al, 2018).…”
Section: Introductionunclassified
“…Wood furniture industry is considered one of the noisiest working environments. Hearing could be adversely affected due to exposure to noise and solvents (5) . Moreover, Batkus et al (6) found that noise levels exceeded the permissible limits in 77% of the surveyed wood furniture workplaces in Lithuania.…”
Section: Introductionmentioning
confidence: 99%